Gambaran Tingkat Aktivitas Fisik Dan Tingkat Kebiasaan Merokok Pada Mahasiswa Kedokteran Universitas Tarumanagara Angkatan 2021-2022 - Nafis Abubakar Jindan; Susy Olivia Lontoh (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Smoking and lack of physical activity are major public health problems, especially among medical students. The aim of this research is to determine the level of physical activity and level of smoking habits among medical students at Tarumanagara University class of 2021-2022. This research is a descriptive observational type and the design used is cross-sectional. Sampling was carried out using non-random sampling, consecutive sampling type. Data collection regarding gender, age, weight, height, physical activity level and level of smoking habits was carried out by carrying out direct measurements and questionnaires to research subject respondents who met the inclusion criteria from the period February-March 2024. The questionnaire was used to measure activity levels physically using the International Physical Activity Questionnaire Short Form (IPAQ-SF). Measuring the level of smoking habits using the Brinkman index questionnaire. The research results showed that the age range of respondents in this study was 18-23 years with a mean of 20.03 years. Respondents who smoked were 38 (62.3%) students and 23 (37.7%) students who did not smoke. The description of the low level of physical activity of Tarumanagara University Medical students was 32 (52.5%) students, 20 (32.8%) students with moderate physical activity and 9 (14.8%) with high physical activity. The level of smoking habits among Tarumanagara University Medical students was low at 59 (96.7%) students and 2 (3.3%) had moderate levels of smoking.